2020
DOI: 10.15381/os.v23i4.18366
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del espesor de los tejidos duros en la dentición permanente humana

Abstract: Objetivo. Verificar el espesor de los tejidos duros dentarios en la actualidad. Métodos. Estudio observacional, descriptivo y transversal. Se utilizaron 94 piezas dentarias permanentes naturales y humanas existente en la morfoteca de la facultad de odontología de la Universidad Nacional del Nordeste y recopiladas durante 2004 al 2014, libres de lesiones, restauraciones, con corona y raíz completas. Se seleccionaron ocho muestras de cada grupo (incisivos, caninos, premolares y molares) para medir el espesor de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Likewise, Wei Y, et al The main advantage of the use of adhesive fixed prostheses is the possibility of making conservative wear on the enamel surface [7]. Affuer M, et al [27], indicated in their study that the average thickness of enamel at the canine level is 2.15mm; therefore, the preparations in this study covered only 1mm of enamel, on the palatal surface of the canine, sufficient space for the lithium disilicate retainer and cement. The present investigation does not agree with the finite element study of Dal Piva A, et al [17], who made more conservative preparations of 0.5mm for lithium disilicate adhesive fixed prostheses.…”
Section: Discussionmentioning
confidence: 73%
“…Likewise, Wei Y, et al The main advantage of the use of adhesive fixed prostheses is the possibility of making conservative wear on the enamel surface [7]. Affuer M, et al [27], indicated in their study that the average thickness of enamel at the canine level is 2.15mm; therefore, the preparations in this study covered only 1mm of enamel, on the palatal surface of the canine, sufficient space for the lithium disilicate retainer and cement. The present investigation does not agree with the finite element study of Dal Piva A, et al [17], who made more conservative preparations of 0.5mm for lithium disilicate adhesive fixed prostheses.…”
Section: Discussionmentioning
confidence: 73%